THE CONCEPT OF HYBRIDIZATION FROM THE PERSPECTIVE OF SCIENCE TEACHING UNDERGRADUATE STUDENTS: A PHENOMENOGRAPHIC STUDY - Cil, Erol; Ugras, Mustafa (Sci Methodical Ctr-Sci Educologica, 2015)
The hybridization of carbon is an important problem of quantum chemistry. It means that atomic orbitals could mix giving hybrid orbitals. Orbitals are not physical objects; they are mathematical solutions of the Schrodinger equation. The aim of this study is to determine through phenomenographic method how Science Teaching undergraduate students comprehend hybridization. 176 students, 78 of whom are male and 98 of whom are female, participated in the study. A semi-structured questionnaire form was used in the study as data collection tool. As a result of analysis of data, it was determined that students describe hybridization in 5 different categories and 4 different ways. According to these categories: 1) Hybridization is a kind of covalent bond, 2) an electronic transition between bonds, 3) an electronic transition between orbitals, 4) the mixing of atomic orbitals to form new orbitals suitable for bonding 5) a case observed as a result of interaction between particles. Among the categories, the one a mixing of atomic orbitals to form new orbitals suitable for bonding category was at the top of the list with 69 metaphors.
Keywords: chemistry education; description category; hybridization; phenomenography; science education